Fluxo de Co2 Proveniente do Rio Tapajós - Tapajós, Raphael; Aguiar, Diego; Junior, Miércio; Machado, Wilderclay; Furtado, Alírio; Figueira, Antônio; Mauro, José; Silva, Rodrigo (Ciência e Natura, 2011)
.